2018
DOI: 10.1007/978-3-319-65798-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Bioimpedance Measurement as a Non-invasive Estimate of Intracranial Pressure

Abstract: These pilot results confirm some degree of relationship between TCB parameters and invasively measured ICP. The magnitude of this relationship is small and, on the basis of the current study, TCB is unlikely to provide a clinically useful estimate of ICP in patients admitted with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Because the penetrability of nearinfrared light on human tissues is very weak, especially the skull, the detection sensitivity of the lesions in the deeper position of the brain is significantly reduced [25]. Bioelectrical impedance technology determines whether the ICP is increased by injecting current into the skull from the skull surface through electrodes and measuring the change in boundary potential [26]. However, in practice, it is difficult to guarantee the electrical contact effect between the electrode and the scalp.…”
Section: Discussionmentioning
confidence: 99%
“…Because the penetrability of nearinfrared light on human tissues is very weak, especially the skull, the detection sensitivity of the lesions in the deeper position of the brain is significantly reduced [25]. Bioelectrical impedance technology determines whether the ICP is increased by injecting current into the skull from the skull surface through electrodes and measuring the change in boundary potential [26]. However, in practice, it is difficult to guarantee the electrical contact effect between the electrode and the scalp.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCBI changes could be detected in babies that suffered intra-partum hypoxia, increased TCBI could not be used to predict neurological outcome (Lingwood et al 2009). In a small trial involving 10 patients, no significant relationship could be found between TCBI and invasively measured ICP (Hawthorne et al 2018). Lingwood and colleagues considered a baseline measurement to be important in assessing TCBI changes in piglets undergoing a hypoxic insult (Lingwood et al 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…An automatic detection algorithm was developed for ICP waveform analysis based on a similar observation as REG pulse wave distortion described here [41]. The relationship between non-invasive multi-frequency transcranial impedance measurements of the brain and skull and ICP in TBI patients in a previous study resulted in no correlation [42]. This type of measurement does not record the pulse wave.…”
Section: Icp and Regmentioning
confidence: 99%